(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: Hotels are increasingly adopting smart technology to boost operational efficiencies, which has effectively reduced employees’ manual workload, it also presents potential negative consequences for work-life balance. Technology’s influence on employee work-life balance is critical for addressing emerging stressors, enhancing overall well-being, and improving retention within the hotel industry. Objectives: This study aims to explore the influence of technology on the work-life balance of Indian hotel industry employees and suggest the scope for improvement concerning the use of technology at the workplace. Methodology: This quantitative study employed a purposive sampling technique to collect data from 128 hospitality professional working in various departments of the hotel industry across India, via a structured questionnaire. Descriptive statistics summarized respondent demographics, while Spearman’s Rank-Order Correlation assessed relationships between technology use perceptions and work-life balance. All analyses were performed using Python. Results: The study revealed that 52% of respondents agreed or strongly agreed that technological tools contributed to reducing workload, and majority of the participants (64%) responded that it improves communication, and simplifying schedule management. However, the findings also highlighted negative consequences, including increased stress (47%), blurred work-life boundaries (51%), and a perceived pressure to remain constantly available (52%). Therefore, most of the participants propose the introduction of flexible work schedules, automation of routine tasks, and implementation of clear availability guidelines. Conclusion: Greater flexibility in work schedules, clearer availability guidelines, and the automation of routine tasks emerged as key technological changes preferred for improving employee’s work-life balance in the Indian hotel industry.